Analysis of the Influence of progressivism education philosophy on the implementation of the free learning curriculum – merdeka campus (MBKM) - Ni Kadek Nita Noviani Pande; Aniek Suryanti Kusuma; Desak Made Dwi Utami Putra; Ayu Gede Willdahlia (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
Education has an important role in shaping humans to become intelligent individuals and able to create quality human resources to face today's modern life. The Independent Campus Learning Policy is an idea to develop education in a better direction by seeking to make the learning process in Higher Education more flexible. The concept of Merdeka curriculum campus Merdeka is very close to the philosophy of progressivism which gives more freedom in the field of education and emphasizes that the education curriculum is not too dense. The purpose of this study was to analyze the influence of the progressive philosophy of learning on the Merdeka curriculum campus Merdeka policy. The method used in this study is the method of studying literature related to education and the theory of the philosophy of progressivism. The results obtained are in the form of an analysis that the philosophy of progressivism is closely related to the Merdeka curriculum campus Merdeka policy in terms of the importance of educational progress so as to provide the best possible benefits to students through the development of interests and talents.